(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Microvessel density is one of the variables that are thought to affect the natural history of prostatic carcinoma in as much as its degree influences tumor progression including the ability of invasion and metastasis. Objectives:To assess microvessel density of prostatic adenocarcinoma, and determine its relationship to serum levels of prostatic specific antigen, and carcinoma grade, as determined by Gleason’s score. Methods: Thirty patients with prostatic adenocarcinoma were studied. Parameters assessed are patients’ age, serum levels of prostatic specific antigen, and the grade of the carcinomas according to (Gleason’s scoring system). The values of the serum levels of prostatic specific antigen and the Gleason score were divided into 3 subgroups for statistical purposes. The degree of angiogenesis was evaluated by assessing microvessel density in sections stained immunohistochemically with CD34. Results:The microvessel density ranged from 10 to 35 (average 20.24 ± 5.95). Statistically significant correlation was found between the mean of microvessel density and serum prostatic specific antigen when the cutoff point of was 11 ng/ml, and with Gleason score when the cutoff point was 7. Conclusion: Microvessel density determination can predict the potential biologic behavior of prostatic adenocarcinoma in individual cases. The incorporation of the serum levels of prostatic specific antigen levels and Gleason scores with the former makes such predictions more practical. Key words: Prostatic adenocarcinoma, microvessel density, serum prostate specific antigen, Gleason score.